Sex differences in chemosensation: sensory or emotional? - Ohla, Kathrin; Lundström, Johan N. (Frontiers in Human Neuroscience, 2013)
Although the first sex-dependent differences for chemosensory processing were reported in the scientific literature over 60 years ago, the underlying mechanisms are still unknown. Generally, more pronounced sex-dependent differences are noted with increased task difficulty or with increased levels of intranasal irritation produced by the stimulus. Whether differences between the sexes arise from differences in chemosensory sensitivity of the two intranasal sensory systems involved or from differences in cognitive processing associated with emotional evaluation of the stimulants is still not known. We used simultaneous and complementary measures of electrophysiological (EEG), psychophysiological, and psychological responses to stimuli varying in intranasal irritation and oldorousness to investigate whether sex differences in the processing of intranasal irritation are mediated by varying sensitivity of the involved sensory systems or by differences in cognitive and/or emotional evaluation of the irritants. Women perceived all stimulants more irritating and they exhibited larger amplitudes of the late positive deflection of the event-related potential than men. No significant differences in sensory sensitivity, anxiety and arousal responses could be detected. Our findings suggest that men and women process intranasal irritation differently. Importantly, the differences cannot be explained by variation in sensory sensitivity to irritants, differences in anxiety or differences in physiological arousal. We propose that women allocate attention stronger to potentially noxious stimuli, which eventually causes differences in cognitive appraisal and subjective perception.